2022
DOI: 10.1002/ese3.1293
|View full text |Cite
|
Sign up to set email alerts
|

Knock combustion characteristics of an opposed‐piston two‐stroke gasoline engine

Abstract: The spark plug of an opposed-piston two-stroke (OP2S) gasoline engine is arranged on the side wall of the cylinder liner, far from the center of the combustion chamber; the ignition core of the mixture is offset, the flame propagation distance is increased, the combustion duration is prolonged, and the knock tendency is severe. In this paper, a quasi-dimensional two-zone combustion model is used in GT-Power software to establish a thermodynamic process simulation model and a knock prediction model is included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Abnormal ignition advance angle will not only reduce the engine performance and deteriorate the fuel economy, but also lead to strong engine detonation, which is a threat to the normal operation of the engine, thus posing a great safety hazard.
Figure 1 Sectional view of the internal structure of the engine 2 .
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal ignition advance angle will not only reduce the engine performance and deteriorate the fuel economy, but also lead to strong engine detonation, which is a threat to the normal operation of the engine, thus posing a great safety hazard.
Figure 1 Sectional view of the internal structure of the engine 2 .
…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, many studies have shown that the ignition advance angle has a great impact on engine knock 7 9 . Ma et al found that with the increase of the ignition advance angle, the pressure and temperature in the cylinder rise rapidly, which increases the possibility of engine knock combustion 2 . Although a slight knock is beneficial to the performance of the engine, if it is uncontrolled and develops into a strong knock, it will reduce the performance of the engine and even cause serious damage to the engine structure.…”
Section: Introductionmentioning
confidence: 99%